PENGARUH PENAMBAHAN PROBIOTIK STARBIO DALAM RANSUM TERHADAP LAJU DIGESTA, BOBOT HATI DAN BOBOT USUS BURUNG PUYUH (COTURNIX COTURNIX JAPONICA). - Lumbantoruan, Mangonar; Siburian , Sedyono Cipto Anthonius (Jurnal Visi Eksakta, 2023)
Sedyono Cipto Anthonius Siburian, 2020. "Addition of Starbio Probiotics in the Ration to Digesta Rate, Heart Weight and Quail Intestine Weight (Coturnix coturnix japonica) under the guidance of Mr. Ir. Mangonar Lumbantoruan, MS as the first supervisor and Mr. Prof. Dr. Ir. Hasan Sitorus, MS as the second supervisor. This research has been carried out in Porlak Simalingkar B Field, Medan Tuntung District, Medan, which took place from August to October 2019. This study aims to determine the effect of adding starbio probiotics in the ration to Digesta Rate, Heart Weight and Quail Intestine Weight (Coturnix coturnix japonica ). The design used in this study was a Completely Randomized Design (CRD) with 5 treatments and 4 replications where each repetition consisted of 200 quails with treatments namely P0 (0 gram Starbio), P1 (2 gram starbio), P2 (4 gram starbio) ), P3 (6 grams of starbio) and P4 (8 grams of starbio) where digesta rate sampling is done on the 20th day and 35th day also 80 liver quail and intestinal weights were taken at 8 weeks. The results showed that the administration had no significant effect on digesta rate, liver weight and bowel weight. The conclusion is the need to increase the level of starbio probiotic administration to maximize the performance of the quail's digestive tract.